Tailors in the processes of faith in the Inquisition Court of Toledo (1483-1597) - Marchant Rivera, Alicia (Documenta & Instrumenta - Documenta et Instrumenta, 2014)
The aim of the present article is to initiate a series of studies about tailors, who, in the most recent historical investigation, have been an object of particular perspectives referred to geographical concrete zones of the Iberian Peninsula. To choose the years between 1483 and 1597, dates of the first and last one of the inquisitorial processes against tailors studied in this work, a total of 73, obeys to the qualitative change that takes place in the Inquisition Court in this stage; moreover the documents from the local Court of Toledo, beside those of Cuenca and Valencia, are the only ones that remain with information about causes previous to 1560. We will examine the group of tailors processed for Jewish, Lutheran or Muslims; the heretical propositions, the blasphemies and the scandalous words in the processes against tailors, to conclude with the incapacitations and the sexual crimes of bigamy. All this will reveal new coordinates with regard to this group: they were taking advantage of favourable socioeconomic circumstances to grow, incorporating other attached professions, or even the intention of belonging to certain circles looking for significance and social distinction.
Keywords: Tailors; Inquisition; Toledo; 15th and 16th centuries